ASSESSMENT OF INVESTMENT ACTIVITY IN RETAIL TRADE IN UKRAINE IN THE CONTEXT OF CHARACTERIZING THE LEVEL OF ITS INVESTMENT ATTRACTIVENESS - TALAH, Yuriy (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article analyzes the issues of functioning and development of the retail trade industry in Ukraine. It is shown that the type of economic activity that is most exposed to the negative impact of macroeconomic crises, shocks and upheavals. Accordingly, in the conditions of a full-scale war, domestic retail trade experienced significant destabilization, including the destruction of enterprises and their infrastructure, retail facilities and warehouse space, and the conditions for product transportation and logistics deteriorated. Thus, the task of forming and implementing a state anti-crisis policy to restore investment activity as a prerequisite for the development of entities of this type of economic activity was actualized. The purpose of the article is to assess investment activity in retail trade in Ukraine in the context of providing a characteristic of the level of its investment attractiveness. The applied significance of the research results lies in the formation of an information and analytical basis for making quality decisions in the system of state policy on the restoration of investment activity in domestic retail trade. The scientific novelty of the research results lies in the further development of the methodology for analyzing the state of development and investment attractiveness of the industry.
Keywords: retail trade; investment activity; investment attractiveness; anti-crisis instruments; state sectoral policy